2005
DOI: 10.1128/aac.49.10.4375-4378.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the MexA and MexB Components of the MexAB-OprM Multidrug Efflux System of Pseudomonas aeruginosa : Identification of MexA Extragenic Suppressors of a T578I Mutation in MexB

Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen characterized by an innate resistance to multiple antimicrobials (6), resistance increasingly attributable, at least in part, to the operation of broadly specific, multidrug efflux systems of the resistance-nodulation-division (RND) family (16). Several RND family multidrug efflux systems have been described in Pseudomonas aeruginosa, although the major system contributing to intrinsic multidrug resistance is encoded by the mexAB-oprM operon (16, 17). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Plasmid pDN40, encoding OprM, was constructed by amplifying the oprM gene from the chromosome of P. aeruginosa K870 via PCR and cloning it (as a SacI-HindIII fragment) into pMMB206. Amplification was achieved using the primers Fragment B-forward (5Ј-GAGCTCGAGCTCTCCA ACGACGTGTTCTTCCAGGT-3Ј; tandem SacI sites are underlined) and OprMR-HindIII [5Ј-AAGCTTAAGCTTAGGCCGA-GCGGGTCCGTGACG C-3Ј; tandem HindIII sites are underlined) and reaction conditions and parameters described previously (extension time increased to 2 min) for the amplification of the EcoRI-tagged mexA gene (30). Plasmid pDN42, encoding MexA(V129M), was constructed by amplifying the mexA(V129M) gene from plasmid pDN7 using the primers pMMB-MexA-For (5Ј-CCCGGGCCCGGGT GAATGTAAGTATTTTGCCTGC-3Ј; tandem SmaI sites are underlined) and pMMB-MexA-Rev (5Ј-GGATCCGGATCCGATCACCCACGCGAAAATGG-3Ј; tandem BamHI sites are underlined) and cloning it (as a SmaI-BamHI fragment) into pMMB206.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Plasmid pDN40, encoding OprM, was constructed by amplifying the oprM gene from the chromosome of P. aeruginosa K870 via PCR and cloning it (as a SacI-HindIII fragment) into pMMB206. Amplification was achieved using the primers Fragment B-forward (5Ј-GAGCTCGAGCTCTCCA ACGACGTGTTCTTCCAGGT-3Ј; tandem SacI sites are underlined) and OprMR-HindIII [5Ј-AAGCTTAAGCTTAGGCCGA-GCGGGTCCGTGACG C-3Ј; tandem HindIII sites are underlined) and reaction conditions and parameters described previously (extension time increased to 2 min) for the amplification of the EcoRI-tagged mexA gene (30). Plasmid pDN42, encoding MexA(V129M), was constructed by amplifying the mexA(V129M) gene from plasmid pDN7 using the primers pMMB-MexA-For (5Ј-CCCGGGCCCGGGT GAATGTAAGTATTTTGCCTGC-3Ј; tandem SmaI sites are underlined) and pMMB-MexA-Rev (5Ј-GGATCCGGATCCGATCACCCACGCGAAAATGG-3Ј; tandem BamHI sites are underlined) and cloning it (as a SmaI-BamHI fragment) into pMMB206.…”
Section: Methodsmentioning
confidence: 99%
“…Mutagenic PCR of the mexA gene was conducted by PCR amplification of the mexA gene from plasmid pDN3, exactly as described previously (30), using the primers JT-28 (5Ј-AAGCTTAAGCTTTGAATGTAAGTATTTTGCCTGC-3Ј; tandem HindIII sites are underlined) and JT-27 (5Ј-GAGCTCGAGCTCGATC ACCCACGCGAAAATGG-3Ј; tandem SacI sites are underlined). The resultant mutagenized mexA-containing PCR products were digested with HindIII and SacI and cloned en masse into pRK415, with the recombinant plasmids electroporated into E. coli S17-1 and mobilized into P. aeruginosa K2275 (⌬mexR ⌬mexA ⌬mexB) harboring plasmid pDN43 [pMMB206::mexB(G220S)] via conjugation as described previously (29).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to earlier predictions that suggested that MFPs might span the periplasm with their N and C termini bound to the inner and outer membranes, respectively (548), the structures suggest that both the N and C termini are likely to lie in close proximity to the inner membrane. Mutagenesis and suppressor analyses suggest that the C termini of the MFPs interact with the inner membrane transporters (at least in the case of the RND transporters Mex and Acr) (139,329,330), while the N terminus may be involved in oligomerization of the MFPs (329).…”
Section: Protein Trafficking Between and Across Membranesmentioning
confidence: 99%